Relationships between sport-specific tests and their validity in predicting the time-motion profile in international taekwondo matches - Apollaro, G.; Panascì, M.; Franchini, E.; Morganti, G.; Ruggeri, P.; Falcó C.; Faelli, E. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The Frequency Speed of Kick Test (FSKT) and the Progressive Specific Taekwondo Test (PSTT) are among the most used sport-specific tests in taekwondo. This study aimed to: (i) investigate the relationship between sport-specific anaerobic (FSKT) and aerobic (PSTT) performance; (ii) evaluate these tests` validity in predicting the time-motion profile in official matches.